Emissions generated by firewood and charcoal consumption in fast-food preparation - Díaz-Nigenda, Emmanuel; Vázquez-Morales, Williams; Venegas Sandoval, Andrea; Morales-Iglesias, Horacio; Hernández Jiménez, Sibia (Ecosistemas y Recursos Agropecuarios, 2021)
The objective of this work was to quantify the emissions of greenhouse gases (GHG) and other pollutants generated by the consumption of firewood and charcoal in the roast chicken preparation in Tuxtla Gutiérrez (TGZ), Chiapas, by applying emission factors (EF). A categorization of establishments was made based on their production and infrastructure used for the activity and then the fuel consumed annually was determined. The gases with higher emissions were carbon dioxide (CO2, 5 312.12 t yr-1) and carbon monoxide (CO, 290.13 t yr-1); while particles with aerodynamic diameters less than 10 μm (PM10) were the most abundant (27.23 t yr-1). Results show the relevance of firewood and charcoal consumption in roast chicken preparation as an air pollution source that adds up to environmental problems of the city.